Additional values of high‐resolution gadoxetic acid‐enhanced MR cholangiography for evaluating the biliary anatomy of living liver donors: Comparison with T2‐weighted MR cholangiography and conventional gadoxetic acid‐enhanced MR cholangiography. Issue 1 (11th April 2017) - Kang, Hyo‐Jin; Lee, Jeong Min; Yoon, Jeong Hee; Joo, Ijin; Chang, Won; Suh, Kyung‐Suk; Lee, Kwang‐Woong; Yi, Nam‐Joon; Han, Joon Koo
Abstract : Purpose: To determine the incremental value of small field of view (sFOV) high‐resolution (HR) gadoxetic acid‐enhanced 3D T 1 ‐weighted (W) magnetic resonance cholangiography (MRC) for evaluating the biliary anatomy of potential living donors by comparing it to T 2 W‐MRC. Materials and Methods: In all, 73 living donor candidates underwent gadoxetic acid‐enhanced MRI (3.0T) including three kinds of MRCs: 3D multislice T 2 W‐MRC, regular FOV (rFOV) (380 × 380mm, resolution 1.0 × 1.2 × 3.0 mm) 3D T 1 W‐MRC, and sFOV (256 × 208 mm, resolution 1.0 × 1.0 × 1.0 mm) HR‐ T 1 W‐MRC. Three radiologists reviewed the image sets for the visibility of segmental intrahepatic bile ducts (BDs), biliary anatomy with its confidence level, and expected number of BD openings at right hemihepatectomy. Results: Compared to T 2 W‐MRC alone, the combination of sFOV HR‐ T 1 W‐MRC and T 2 W‐MRC (s T 1 W‐HR set) yielded significantly improved BD visibility scores ( P < 0.01) and confidence levels for biliary anatomy ( P < 0.01). Compared to the r T 1 W set (rFOV T 1 W‐MRC with T 2 W MRC), the sFOV HR set showed significantly increased caudate duct visibility ( P < 0.001). In the case of T 2 W‐MRC presenting subdiagnostic image quality, the addition of sFOV HR T 1 W‐MRC provided diagnostically acceptable image visibility (53.8∼90%) to all reviewers. The addition of sFOV HR‐ T 1 W‐MRC resulted in a significantly higher consistency with the operative record and expected number of BD openings than did T 2 W‐MRC alone ( P < 0.05 in all reviewers) or rFOV set ( P < 0.05 in one reviewer) with excellent interobserver agreement of both T 1 W‐MRC sets. Conclusion: The combination of sFOV HR‐ T 1 W‐MRC and T 2 W‐MRC significantly improved BD visibility and confidence levels for biliary anatomy compared to T 2 W‐MRC alone, thereby allowing accurate biliary anatomy assessment in most patients with subdiagnostic T 2 W‐MRC images. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:152–159.